Situating Indonesian Pesantren within Literacy Practice and Religious Moderation in Post-Truth Era - Raudhatun Nafisah; Faisal Husen Ismail; Syaiful Hisyam Saleh (IJELR: International Journal of Education, Language, and Religion, 2022)
This paper delves into the contemporary dynamics characterizing the educational practices of Islamic boarding schools (pesantren) in Indonesia, focusing on their intersection with literacy practices and the principles of religious moderation. Indonesia's pesantren system has been a cornerstone of Islamic education for centuries, and this study seeks to shed light on how these traditional institutions are adapting to modern contexts while preserving their core values. Through a comprehensive analysis of literature and theories, we argue on the multifaceted ways in which literacy practices are integrated into the curriculum of pesantren, enabling students to engage effectively with both religious texts and broader educational content. Moreover, we also explore how these literacy practices align with the principles of religious moderation, fostering an environment that promotes tolerance, dialogue, and ethical conduct among students in a modern world.